Effects of a Low-Carbohydrate Ketogenic Diet on Reported Pain, Blood Biomarkers and Quality of Life in Patients with Chronic Pain: A Pilot Randomized Clinical Trial. Issue 2 (17th September 2021) - Field, Rowena; Pourkazemi, Fereshteh; Rooney, Kieron
Abstract: Background: A low-carbohydrate ketogenic diet has been reported to improve chronic pain by reducing inflammation, oxidative stress, and sensitivity within the nervous system. The main aim of this trial is to evaluate the effects of a ketogenic diet on reported pain, blood biomarkers and quality of life in patients with chronic pain. Methods: Participants with chronic musculoskeletal pain were recruited for a 12-week diet intervention that commenced with a 3-week run-in diet removing ultra-processed foods, followed by randomization to either a whole-food/well-formulated ketogenic diet (WFKD) or to continue with the minimally processed whole-food diet (WFD). Outcome measures included: average pain (visual analogue scale VAS), blood biomarkers, anthropometrics, adherence, depression, anxiety, sleep, ketones, quality of life, diet satisfaction, and macronutrient intake. Results: Average weekly pain improved for both groups. WFKD group VAS reduced by 17.9 ± 5.2 mm ( P = .004) and the WFD group VAS reduced 11.0 ± 9.0 mm ( P = .006). Both groups also reported improved quality of life (WFKD = 11.5 ± 2.8%, P = .001 and WFD = 11.0 ± 3.5%, P = .014). The WFKD group also demonstrated significant improvements in pain interference ( P = 0.013), weight ( P < .005), depression ( P = .015), anxiety ( P = .013), and inflammation (hsCRP) ( P = .009). Significant average pain reduction remained at three-month follow-up for both groups (WFKD P = .031, WFD P = .011). Conclusions: The implementation of a whole-food diet that restricts ultra-processed foods is a valid pain management tool; however, a low-carbohydrate ketogenic diets may have potentially greater pain reduction, weight loss and mood improvements.